Optimalisasi Pengelolaan Sumber Daya Pendidikan di Sekolah Melalui Program Pengabdian Masyarakat: Perspektif Penguatan Manajemen Berbasis Sekolah - Hanafiah, Hanafiah (Civiliza Publishing, 2024)
This study aims to look at the management of educational resources in schools. We launched a community service program. It focuses on strengthening school-based management (SBM). Using qualitative methods and descriptive approaches, this study combines various techniques. From in-depth interviews to careful observation, to document analysis, all have been done. This study was conducted at the energetic SMP N 5 Jogjakarta. The findings show that the management of educational resources can soar higher. The key? Harmonious collaboration between schools and communities. In addition, the application of SBM principles—independence, partnership, participation, openness, and accountability—is the road to success.